Diagnostic performances of lung ultrasound associated with inferior vena cava assessment for the diagnosis of acute heart failure in elderly emergency patients: a diagnostic study. (11th November 2020) - Balen, Frederic; Houze Cerfon, Charles-Henri; Lauque, Dominique; Hebrad, Manon; Legourrierec, Thibault; Delmas, Clement; Charpentier, Sandrine
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and importance: Few studies are looking at the usefulness of lung ultrasound combined with inferior vena cava (ultrasound strategy) in the particularly challenging diagnosis of acute heart failure (AHF) in elderly dyspneic patients attending the emergency department (ED). Objective, design, settings, and participants: This was a prospective diagnostic study conducted in two French EDs from December 2015 to March 2019, aimed to determine the accuracy of an ultrasound strategy for the diagnosis of AHF in the elderly. Patients aged 65 and older referred to the ED for dyspnea were screened for inclusion. Intervention: An emergency physician, blinded to the first findings, performed chest ultrasound, and assessment of inferior vena cava (ultrasound strategy). Outcome measure and analysis: The primary endpoint was a final diagnosis of AHF, adjudicated by two independent experts after reviewing the entire medical record. The sensitivity and specificity of ultrasound and standard strategies were calculated. Main results: A total of 116 patients were included, mean age 84 years (SD 9). Among them, there were 76 (66%) cases of AHF and 51 (44%) cases of pneumonia. The ultrasound work up had a sensitivity of 82% [95% confidence interval (CI), 71–90] and a specificity of 68% (95% CI, 51–90] for AHF. The standard strategy had a sensitivity of 92% (95% CI, 84–97) and a specificity of 53% (95% CI, (36–68). Conclusions: In this prospective study, there was no statistically significant difference between point-of-care ultrasound and a combination of clinical, radiographic, and biological findings for the diagnosis of acute heart failure.